2020
DOI: 10.1159/000507418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on General and Central Obesity: Results from 20 Randomized Controlled Trials Involving Apparently Healthy Populations

Abstract: Background: The obesity pandemic has been paralleled by a high prevalence of vitamin D deficiency (VDD). There is growing epidemiological evidence linking low vitamin D status with obesity events. In addition, observational studies also show that obesity may increase the risk of VDD. However, there is insufficient knowledge to understand whether there is a causality between the two. Moreover, the impact of vitamin D supplementation on obesity indices has shown inconsistent outcomes. Objective: This meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
3
35
0
1
Order By: Relevance
“…Additionally, here we found that group B had the lowest improvement in BMI. The improvement in this group might be to the effect of a balanced low-calorie diet only as the vitamin D supplementation alone had no significant effect on BMI; this was in line with the recent systemic review that reported that despite increased serum 25(OH) D levels, the obesity indices (BMI, Waist Circumference and Waist hip Ratio) did not improve [55].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, here we found that group B had the lowest improvement in BMI. The improvement in this group might be to the effect of a balanced low-calorie diet only as the vitamin D supplementation alone had no significant effect on BMI; this was in line with the recent systemic review that reported that despite increased serum 25(OH) D levels, the obesity indices (BMI, Waist Circumference and Waist hip Ratio) did not improve [55].…”
Section: Discussionsupporting
confidence: 87%
“…Other meta-analyses suggest that vitamin D supplementation may have beneficial effects on adiposity in certain populations, with sub-group analyses of 20 randomized clinical trials (n = 3,153 participants) suggesting reduced body mass index and waist circumference in women living in Asian countries supplemented for ≥ 6 months (243). Multi-omic analyses of published datasets have identified vitamin D (among a suite of other candidates) as a potential prophylactic agent for COVID-19 (244).…”
Section: Vitamin D Status and Covid-19mentioning
confidence: 99%
“…It has been proposed that an inverse relationship exists between vitamin D serum levels and BMI (21). As was pointed out in the introduction to this paper, low serum 25(OH)D in obese patients can occur for a number of reasons including insu cient vitamin D consumption, increased fat or muscle mass, genotype variation in vitamin D binding proteins or enzymes responsible for vitamin D metabolism (11,13). On the other hand, vitamin D de ciency can increase the risk of developing depression, through several biological pathways including effects on immunomodulation, cellular signaling, modulation of hypothalamic-pituitary-adrenal axis, intracellular calcium homeostasis, and production of neurotransmitters(6, 22) Moreover, both obesity and vitamin D de ciency lead to a chronic low-grade in ammation, which has been suggested to contribute to the development of depression (11,23).…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that vitamin D de ciency is 35% more likely in obese people compared to the healthy-weight subjects (12).Volumetric dilution of Vitamin D is the most plausible mechanism of low 25(OH)D in individuals with obesity (11). Alternative mechanisms for lower 25(OH)D concentrations in patients with obesity include lower dietary consumption, decreased dermal synthesis, reduced intestinal absorption, altered metabolism, as well as less sunlight exposure due to lower physical activity (13).…”
Section: Introductionmentioning
confidence: 99%